Focusing particles by induced charge electrokinetic flow in a microchannel. Issue 4 (February 2016) - Song, Yongxin; Wang, Chengfa; Li, Mengqi; Pan, Xinxiang; Li, Dongqing
Abstract : A novel method of sheathless particle focusing by induced charge electrokinetic flow in a microchannel is presented in this paper. By placing a pair of metal plates on the opposite walls of the channel and applying an electrical field, particle focusing is achieved due to the two pairs of vortex that constrain the flow of the particle solution. As an example, the trajectories of particles under different electrical fields with only one metal plate on one side channel wall were numerically simulated and experimentally validated. Other flow focusing effects, such as the focused width ratio (focused width/channel width) and length ratio (focused length/half‐length of metal plate) of the sample solution, were also numerically studied. The results show that the particle firstly passes through the gaps between the upstream vortices and the channel walls. Afterwards, the particle is focused to pass through the gap between the two downstream vortices that determine the focused particle position. Numerical simulations show that the focused particle stream becomes thin with the increases in the applied electrical field and the length of the metal plates. As regards to the focused length ratio of the focused stream, however, it slightly increases with the increase in the applied electrical field and almost keeps constant with the increase in the length of the metal plate. The size of the focused sample solution, therefore, can be easily adjusted by controlling the applied electrical field and the sizes of the metal plates.